Estimating the clinical and economic burden of medically attended influenza in South Korea, stratified by age and comorbidity: A five-season hospital-based surveillance data, 2014/15–2018/19 - Choi, Min Joo; Choi, Won Suk; Song, Joon Young; Cheong, Hee Jin; Noh, Ji Yun; Wie, Seong-Heon; Lee, Jin Soo; Lee, Jacob; Kim, Hyo Youl; Kim, Shin-Woo; Park, Kyong-Hwa; Kim, Woo Joo (PloS one, 2025)
This study aims to estimate the clinical and economic burden of influenza in South Korea across five seasons (2014/15-2018/19), stratified by age and comorbidity, using data from the Hospital-based Influenza Morbidity and Mortality (HIMM) network. Data were gathered from eight university hospitals and included adults (≥ 20 years) with laboratory-confirmed influenza. The catchment population was estimated using hospital and national statistical data. Economic costs were evaluated from a societal perspective. The incidence of medically attended influenza ranged from 113.1 to 220.7 per 100,000 adults, with hospitalization rate of 35.5 to 76.8, intensive care unit admission at 4.2 to 9.2, and deaths at 1.4 to 3.6. Annual socioeconomic costs ranged from $156 to $316 million, primarily driven by indirect costs associated with early mortality. The highest cost was recorded in 2017/18, following the largest outbreak, particularly among older adults. Per capita socioeconomic costs ranged from $2,747 to $4,072 across the seasons, with peak values observed in 2018/19 and 2015/16. Among at-risk groups, per capita costs were 1.5-2.3 times higher than those of the general adult population. Influenza imposes a significant clinical and economic burden on South Korea. Tailored strategies are essential to mitigate this burden, particularly among older adults and at-risk individuals not covered by the National Immunization Program.